2014
DOI: 10.1016/j.rbmo.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and sperm preparation on the quality of spermatozoa

Abstract: .be (A Thijssen).Annelies Thijssen graduated in July 2012 with a Masters in biomedical sciences -clinical molecular sciences from the Transnational University Limburg, Diepenbeek, Belgium. She finished her master thesis on 'Methods for optimal sperm selection and preservation in the IVF laboratory' at the Genk Institute for Fertility Technology of the Ziekenhuis Oost-Limburg, Genk, Belgium. In September 2012, she started a PhD project 'Sperm banking in Belgium: medical, ethical and economical aspects', a colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 33 publications
7
22
0
1
Order By: Relevance
“…However, the survival rate of spermatozoa at RT did not significantly decline. In agreement with our data, Thijssen et al () showed that incubation at RT resulted in significantly less apoptotic and dead spermatozoa compared with testis temperature (35°C). Incubation at 37°C decreased sperm viability and motility to a greater extent than incubation at RT.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the survival rate of spermatozoa at RT did not significantly decline. In agreement with our data, Thijssen et al () showed that incubation at RT resulted in significantly less apoptotic and dead spermatozoa compared with testis temperature (35°C). Incubation at 37°C decreased sperm viability and motility to a greater extent than incubation at RT.…”
Section: Discussionsupporting
confidence: 93%
“…Epigenetic spermatozoa abnormalities such as aberrant DNA methylation patterns and reprogramming errors can impact both fertilisation rate and pre‐implantation embryo development (Emery & Carrell, ). Previous studies have shown that incubation of spermatozoa at various temperatures affects spermatozoa parameters such as motility (Matsuura et al, ), survival (Thijssen et al, ) and reactive oxygen species (ROS) levels (Esfandiari et al, ). However, no published study has addressed the changes in DNA methylation after extended incubation.…”
Section: Introductionmentioning
confidence: 99%
“…Thijssen et. al and Petrella et al reported and also we observed in our study, that the motility of washed sperm decreases with prolonged incubation at both room temperature and at 37°C [2,16]. We attribute the more severe motility decrease observed at 37°C to the faster biological reactions as an effect of temperature, and it is a phenomenon consistent with the literature [17].…”
Section: Discussionsupporting
confidence: 92%
“…The present study demonstrated a significantly better and longer retention of spermatozoa motility when washed samples were incubated at room temperature (22°C) for 24 hrs compared to the control held at 37°C, and at other holding temperatures in both protein-free and protein-containing culture media. This finding was supported by the observations of Thijssen (Thijssen et al 2014) who observed better spermatozoa quality in washed spermatozoa samples incubated at room temperature than in those incubated at 37°C. The attempt to retain optimal spermatozoa motility over a short period of time by reducing the holding temperature to 15°C proved to be of no benefit.…”
Section: Discussionsupporting
confidence: 80%